Analisis Faktor-faktor yang Mempengaruhi Keputusan Pria dalam Menggunakan Skincare - Nisa, Azatul Khairun; Saputra, Indra (TSAQOFAH, 2025)
The emergence of negative stigma toward men who use skincare, despite growing awareness of the importance of facial care, reflects a persistent barrier rooted in gender perceptions. This study aims to analyze the factors influencing men's decisions to use skincare products. A quantitative method was employed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The research sample consisted of 93 male students from the Faculty of Tourism and Hospitality at Universitas Negeri Padang, all of whom were active skincare users. Data were collected through an online questionnaire distributed via Google Form and analyzed using SmartPLS 4 to assess both direct and indirect relationships among variables. The findings indicate that psychological factors, economic and product-related factors, informational media, and situational factors directly influence men's skincare usage decisions, while demographic and social factors do not have a direct effect. Furthermore, social, economic and product-related, and situational factors indirectly influence decisions through the mediation of informational media. These findings offer empirical insights into the determinants of male consumer behavior in skincare usage and have implications for marketing strategies that are responsive to gender-related issues.